2016
DOI: 10.1073/pnas.1600474113
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A-aldehyde adducts: AMD risk and targeted therapeutics

Abstract: Although currently available treatment options for age-related macular degeneration (AMD) are limited, particularly for atrophic AMD, the identification of predisposing genetic variations has informed clinical studies addressing therapeutic options such as complement inhibitors and anti-inflammatory agents. To lower risk of early AMD, recommended lifestyle interventions such as the avoidance of smoking and the intake of low glycemic antioxidant-rich diets have largely followed from the identification of nongen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…4 An increasing body of evidence suggests that bisretinoid adducts derived from atRAL constitute the primary components of RPE lipofuscin, 1,24-28 and they have been identified as potential pathogenic factors in STGD1 and AMD. 28,29 A2E, a bisretinoid lipofuscin chromophore of RPE, reportedly activates NLRP3 inflammasome signaling in ARPE-19 cells. 30 In this study, we demonstrated that the A2E precursor atRAL activated NLRP3 inflammasome to trigger pyroptosis and apoptosis of ARPE-19 cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…4 An increasing body of evidence suggests that bisretinoid adducts derived from atRAL constitute the primary components of RPE lipofuscin, 1,24-28 and they have been identified as potential pathogenic factors in STGD1 and AMD. 28,29 A2E, a bisretinoid lipofuscin chromophore of RPE, reportedly activates NLRP3 inflammasome signaling in ARPE-19 cells. 30 In this study, we demonstrated that the A2E precursor atRAL activated NLRP3 inflammasome to trigger pyroptosis and apoptosis of ARPE-19 cells (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fenretinide (4-hydoxy[phenyl]retinamide) is a retinoid derivative that competes with retinol for binding to retinol binding protein 4 (RBP4), thus reducing the delivery of all-trans-retinol to the RPE. 66,67 In contrast, the treatment emixustat (a derivative of all-trans-retinylamine) is a retinol mimic that inhibits the action of isomerohydrolase RPE65, Percentages given relate to total number in each cohort that completed the entire study duration (intervention, 20; control, 27). ''Growth/ shrinkage'' defines participants for whom an increase/decrease in drusen volume was reported over 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…67,68 The hypothesis with both of these treatments, and other visual cycle modulating agents, is that, through slowing the visual cycle and the consequent reduction in formation of the toxic bisretinoid fluorophore A2E found in RPE lipofuscin, AMD progression will be slowed. 66,67,[69][70][71] Trial results for fenretinide did not show a statistically significant difference in geographic atrophy lesion size compared with placebo and the trend toward reduced lesion growth rates in those where RBP levels dropped below 2 mg/dL was also not statistically significant. 66 Similarly, a phase 2b/3 trial of emixustat in the treatment of geographic atrophy failed to reach its primary endpoint.…”
Section: Low-level Nighttime Light Therapy For Amdmentioning
confidence: 99%
“…The Dowlings report that that treatment with antioxidants for "dry" AMD and anti-VEGF therapy for "wet" AMD have had modest success. Some recent work suggests that treatments useful in lysosomal storage diseases or that complement antagonists are also worth a shot (6).…”
Section: The Macula Degeneratesmentioning
confidence: 99%